Refractive Sacramentalities: Islamic and Christian Worship and Friendship - Hopkins, Megan (Concilium, 2025)
God is evident in all creation as understood by both Muslims and Christians. While the term "sacramentality" does not cross the border from Christianity to Islam, conceptually it is evident each tradition. This contribution situates the concept of sacramentality in Christianity among God, humanity, and the natural world; and explores the relationship between Creator and creation, servant and worship in Islam. Primary focus is placed on worship and embodied experiences in each tradition. This comparison yields similarities, however undergirded by deeper doctrinal differences. Conclusions are oriented toward an expansive understanding of both sacramentality and 'ayat (signs) in interreligious friendship.